Management of tyrosine kinase inhibitors (TKI) side effects in differentiated and medullary thyroid cancer patients. Issue 3 (June 2017) - Resteghini, C.; Cavalieri, S.; Galbiati, D.; Granata, R.; Alfieri, S.; Bergamini, C.; Bossi, P.; Licitra, L.; Locati, L.D.
Abstract : Four tyrosine kinase inhibitors (TKIs) have been recently licensed in thyroid cancer (TC), sorafenib and lenvatinib for differentiated TC, vandetanib and cabozantinib for medullary TC. Others TKIs such as axitinib, pazopanib, sunitinib, have been tested within phase II trials. The toxicity burden associated to TKIs is not negligible. Drug reductions and interruptions are common, definitive drug withdrawals have also been reported as well as toxic deaths in more rare cases. In this context, the prevention of toxicities is mandatory to allow patients to stay on treatment as long as possible without dose and schedule modifications. Both physicians and patients should be educated to recognize drug-related toxicities in order to manage them in an early phase. Tools (e.g. toxicities summary booklet) for physicians and patients could be considered to improve the knowledge on side effects management. Guidelines, whenever available, should be followed.